Global management : universal theories and local realities - Management center Europe; . (London : Thousand Oaks, CA : Sage Publications, 1994)
This book contains some of the economics principles for European countries.
Papers presented at a conference, Cuernavaca, Mexico, 1995.
Includes bibliographical references
asm; 24/01/19
Loans
Keywords: International business enterprises; Strategic alliances (Business)